Study of Bond Properties of Steel Rebars with Recycled Aggregate Concrete. Analytical Modeling - Rafi, M.M. (Проблемы прочности, 2019)
The results of analytical analysis of interfacial bond stress-slip behavior of steel bars embedded in recycled aggregate concrete (RAC) are reported in this paper. Significantly large data from the laboratory pullout tests of specimens were analyzed including the specimens tested by the author. A bond stress-slip constitutive law is proposed for the steel rebars embedded in RAC. The experimental stress–slip responses of specimens were compared with the theoretical predictions. An existing model in the literature was employed for determining the ascending branch of the bond stress–slip curve. Based on the differences in the observed and predicted responses, a modified expression to capture the descending branch of the bond stress–slip curve was proposed. The results of the modified expression correlated well with the observed data of samples tested by the author and those reported in the existing literature.